SYST-14 CLINICAL EFFICACY OF ONC201 IN RECURRENT H3 K27M-MUTANT DIFFUSE MIDLINE GLIOMA (DMG) PATIENTS. (5th August 2022) - Arrillaga-Romany, Isabel; Kurz, Sylvia; Tarapore, Rohinton; Lu, Guangrong; Sumrall, Ashley; Butowski, Nicholas; Harrison, Rebecca; DeGroot, John; Chi, Andrew; Shonka, Nicole; Umemura, Yoshie; Odia, Yazmin; et al.
Abstract: BACKGROUND: H3 K27M-mutant DMG predominantly affects children and young adults; no effective therapy is known. ONC201 is a first-in-class, anti-cancer DRD2 antagonist and ClpP agonist. METHODS: Fifty pediatric and adult patients with recurrent H3 K27M DMG who received oral ONC201 monotherapy in clinical trials and expanded access were selected for a planned efficacy analysis. Eligibility criteria included measurable contrast-enhancing disease by RANO-HGG criteria (excluding pontine and spinal cord tumors), KPS/LPS≥60, ≥90 days from prior radiation, and adequate washout from prior anti-cancer therapy. The primary endpoint was overall response rate (ORR) by RANO-HGG criteria. Secondary endpoints included duration of response, time to response, progression-free survival (PFS), overall survival (OS), corticosteroid response rate, performance status response rate, and ORR by RANO-LGG criteria. Radiographic endpoints were assessed by dual-reader blinded independent central review. Data cutoff was May 31, 2021. RESULTS: ORR was 20.0% (95%CI, 10.0–33.7) by RANO-HGG criteria. Median duration of response was 11.2 months (95%CI, 3.8–not reached) and median time to response was 8.3 months (range, 1.9–15.9). PFS at 6 months was 35.1% (95%CI, 21.2–49.3). The ORR was 26.0% (95%CI, 14.6–40.3) by RANO-LGG criteria. Fifteen patients (30.0%; 95%CI, 17.9–44.6) achieved an objective response by RANO-HGG and/or RANO-LGG criteria. Of 15 patients receiving ≥4 mg daily dexamethasone at baseline, 7 (46.7%; 95%CI, 21.3–73.4) achieved ≥50% confirmed reduction in dose. Of 34 patients with baseline KPS/LPS <80, 7 (20.6%; 95%CI, 8.7–37.9) achieved a confirmed performance status improvement. With a median follow-up of 18.8 months, median OS was 13.7 months (95%CI, 8.0–20.3) and OS at 24 months was 34.7% (95%CI, 20.7–49.2). Twenty-five patients had serious adverse events with one possibly related to ONC201 by investigator assessment. CONCLUSIONS: ONC201 monotherapy exhibits durable and clinically meaningful efficacy in recurrent H3 K27M-mutant DMG.